Does Shifting Surgeries from Inpatient to Outpatient Settings Save Money? The Case of Hysterectomy in Massachusetts. (20th August 2020) - Fonkych, K.; Nasuti, L.; Gaddam, S.; Auerbach, D.
Abstract : Research Objective: Technological advances have allowed for the shifting of many surgeries from hospital inpatient to outpatient settings. This shift should lead to net cost savings as fewer resources are required. There could also be distributional and other market consequences due to differences in referral patterns, individual hospital resources, and benefit design. Scheduled hysterectomies (eg, those that are unrelated to maternity episodes) represent an example of this trend. The objective of this study is to analyze the impact of shifting surgeries from inpatient to outpatient settings of care on the distribution of surgeries across types of hospitals and on overall costs. Study Design: We identified hysterectomies performed in Massachusetts in both inpatient and outpatient settings among members of five large private insurers in the state's all‐payer claims database from 2015 to 2017. We further subset these procedures to define "shiftable" hysterectomies as procedures that were not maternity related or related to cancer and did not involve major complications. We estimated the average payment for the hysterectomy episode which was defined to include all claims taking place on the same day as the procedure and included both hospital and professional payments. We grouped hospitals by type and system to evaluate the distributional effects of inpatient to outpatient shifts. Population Studied: Commercially insured inpatient stays and outpatient surgery encounters for hysterectomies in Massachusetts during 2015‐2017 period. Principal Findings: Despite shifting of about one‐fifth of inpatient hysterectomies to outpatient settings, the average system‐wide payment per hysterectomy in our commercially insured population increased 9.5% over the study period. When examined in more detail, this paradox appears to be partly explained by a shift from hospitals with lower‐than‐average‐priced inpatient and outpatient surgeries to hospitals with higher‐than‐average priced outpatient surgeries. Absent such a shift, total spending would have increased only 6.3% due to price increases within settings. For example, the average payment for an outpatient hysterectomy procedure at one of the AMCs with highest increase in outpatient hysterectomies, while lower than the cost of a procedure on their own inpatient wards, was 37% higher than the inpatient cost of the procedure at a local community hospital that lost the most inpatient volume. Overall, nonteaching hospitals, especially those with a high mix of public payers, lost commercial hysterectomy volume, and consequently revenue, while outpatient hysterectomies accumulated in a handful of academic hospital systems. Conclusions: The promise of shifting surgeries to outpatient settings to reduce total spending has not materialized for hysterectomy—a surgery that underwent a dramatic shift in just 2 years. However, there are winners and losers among providers. The financial well‐being of community hospitals may partly depend on their ability to retain their commercial volume in their own outpatient settings. Implications for Policy or Practice: Hysterectomy as a case study suggests that the promise of more efficient modes of care delivery may not yield net savings to consumers if high‐priced systems capture a large share of the shifted volume. Primary Funding Source: Xxxx.